A retrospective cohort study of shift work and risk of incident cancer among German male chemical workers - Mei Yong; Maria Blettner; Katharina Emrich; Michael Nasterlack; Christoph Oberlinner; Gaël P Hammer (Nordic Association of Occupational Safety and Health (NOROSH), 2014)
OBJECTIVE: Human evidence of carcinogenicity concerning shift work is inconsistent. This industry-based cohort study aimed to examine the relationship between working in a rotating shift and cancer incidence. METHODS: The cohort consisted of male production workers (12 609 shift and 15 219 day), employed in a large chemical industry for at least one year between 1995-2005, and residing in the German federal state of Rhineland-Palatinate. Incident cancer cases from 2000-2009 were identified through record linkage with the cancer registry of Rhineland-Palatinate. Information on exposure to shift work and potential confounders, including age, smoking status, job level, and employment duration, was extracted from the personnel and health records. Cox proportional hazard models were used to estimate hazard ratios (HR) with 95% confidence interval (95% CI) adjusted for potential confounders. RESULTS: Between 2000-2009, 518 and 555 cancer cases (excluding non-melanoma skin cancer) occurred among shift and day work employees, respectively. Compared to "never shift work", shift workers experienced an increased risk of cancers neither at all-sites (HR 1.04, 95% CI 0.89-1.21) nor for prostate cancer in particular (HR 0.93, 95% CI 0.71-1.21). The risks of leukemia and esophagus cancer were increased if smoking was not taken into account, albeit based on small numbers. However, adjusting for smoking changed the HR and the risk diminished. CONCLUSIONS: Our analyses do not provide evidence for a carcinogenic effect of the shift system under study.